Hubungan Sikap dan Tindakan Petani Tembakau dengan Kadar Pestisida dalam Darah di Kecamatan Pleret Kabuoaten Bantul Tahun 2012 - Nawang Dwi Nurani; Bambang Suwerda; Lilik Hendrarini (Poltekkes Kemenkes Yogyakarta, 2013)
The use of chemical pesticide in order to control pest problems in crops which is related withpeople’s demand is unavoidable. However, inappropriate use of pesticide will lead to bad impacton human health and the environment. The study was aimed to know the relationship betweenpesticide related attitude and practice of tobacco farmers in Kelurahan Pleret Kecamatan Bantuland pesticide concentration in their blood by conducting a cross sectional approached survey.The sample was all 65 tobacco farmers in the study area. Blood pesticide level was measuredby cholinesterase method, meanwhile the attitude and practice were measured by using aquestionnaire. The results showed that only 7,69 % farmers had normal pesticide concentrationin their blood, and only 43,07 % and 41,53 % farmers had positive attitude and good practicerelated with pesticide use. The subsequent statistical tests revealed that both independent variables were significantly assciated with the blood pesticide level, with p values 0.016 and0.018, respectively. Based on these findings, the tobacco farners are advised to: attend the regular counseling held by the agriculture information office, pay attention on occupational helathand safety, use fully personal protection devices when handling pesticide spraying, and washvegetables and and fruits thoroughly before cooking or eating.